DAMPAK NUTRISI TERHADAP KINERJA ATLET DI BERBAGAI CABANG OLAHRAGA DI NUSA TENGGARA TIMUR (NTT) - Salmon Runesi; Michael Johannes Hadiwijaya Louk; Ratno Susanto; Ronal Dwi Ardian Fufu; Al Ihzan Tajuddin; Dilli Dwi Kuswoyo (Jurnal Porkes, 2025)
This study aims to examine the impact of nutrition on athlete performance when performing sports activities. This research uses qualitative descriptive research. Data collection on athletes' eating habits is often done using questionnaires to obtain accurate and systematic information on daily nutritional consumption patterns. Analyzing the relationship between nutrition and athlete performance is an important step to understanding how nutritional intake affects physical and mental abilities in sports. The population in this study was all athletes actively competing in various sports in East Nusa Tenggara and the study sample was 90 athletes. Overall, the data showed that regular eating habits, balanced nutritional intake (especially vegetables, fruits, and protein), and restriction of fast food and sugary/soda drinks contributed positively to athletes' performance. In conclusion, nutrition was shown to play an important role in improving athlete performance in East Nusa Tenggara. Research shows that a balanced consumption of carbohydrates, protein, fat, and vitamins and minerals helps athletes maintain energy, accelerate recovery, and improve endurance. Most athletes ate three meals a day, regularly ate breakfast, and consumed vegetables and fruits daily, which overall contributed positively to their performance.